2015
DOI: 10.3109/10641963.2015.1060991
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between arterial stiffness and sleep architecture in patients with essential hypertension

Abstract: A change in sleep architecture might increase the risk of hypertension and worsen target organs. This study thus aimed to study the features of sleep architecture and examine its relationship with pulse wave velocity (PWV), a measure of arterial stiffness, in patients with essential hypertension and healthy people aged 45-65 years (n = 106). We collected data on demographics, the serum index, overnight polysomnography, vascular testing and ambulatory blood pressure in addition to measuring arterial stiffness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that sleep restriction leads to an imbalance of appetite-regulating hormones that may result in increased food intake [ 6 ]. The increased hunger may be satisfied by unhealthy food choices that impair cardiovascular health, which could potentially increase arterial stiffness, an effect that is also caused by sleep problems themselves [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that sleep restriction leads to an imbalance of appetite-regulating hormones that may result in increased food intake [ 6 ]. The increased hunger may be satisfied by unhealthy food choices that impair cardiovascular health, which could potentially increase arterial stiffness, an effect that is also caused by sleep problems themselves [ 12 ].…”
Section: Introductionmentioning
confidence: 99%